A generic platform for scalable access to multimedia-on-demand systems. - Boutaba, R. (IEEE Journal on selected areas in communications)
Access to multimedia servers is commonly done according to a client/server model where the end user at the client host retrieves multimedia objects from a multimedia server. In a distributed environment, a number of end users may need to access a number of multimedia servers through one or several communication networks. Such a scenario reveals the requirement for a distributed access platform. In addition, the demand for multimedia information is increasing beyond the capabilities of high performance storage devices. Therefore, load distribution and scalability issues must be addressed while designing and implementing the distributed access platform. This paper introduces a scalable access platform (SAP) for managing user access to multimedia-on-demand systems while optimizing resource utilization. The platform is generic and capable of integrating heterogeneous multimedia servers. SAP operation combines static replication and dynamic load distribution policies. It provides run time redirecting of client requests to multimedia servers according to the workload information dynamically collected in the system. To support multimedia-on-demand systems with differing quality-of-service (QoS) requirements, the platform also takes into account, as part of the access process, user QoS requirements and cost constraints. This paper also presents an application of the generic platform implementing a scalable movie-on-demand system, called SMoD. Performance evaluation based on simulation shows that in many cases SMoD can reduce the blocking probability of user requests, and thus can support more users than classical video-on-demand (VoD) systems. It also shows that the load is better distributed across the video servers of the system